DEVELOPMENT OF A MATHEMATICS LEARNING MODULE WITH THE MISSOURI MATHEMATICS PROJECT (MMP) MODEL ON THE TOPIC OF ALGEBRAIC FUNCTION LIMITS FOR GRADE XI MA AL-JUNAIDIYAH, DISTRICT MANDAILING NATAL - Febri Tanjung; A. Naashir M. Tuah Lubis; Sakinah Siregar (PT. Jurnal Center Indonesia Publisher, 2025)
This research is driven by the limited use of mathematics learning tools such as teaching modules in schools. At MA Al-Junaidiyah in Mandailing Natal Regency, learning still largely relies on textbooks based on the 2006 curriculum, resulting in low student achievement in mathematics, particularly in the topic of algebraic function limits. This study aims to determine the validity, practicality, and effectiveness of a Mathematics Learning Module developed using the Missouri Mathematics Project (MMP) Model for the topic of Algebraic Function Limits for Grade XI students at MA Al-Junaidiyah. The research follows the Research and Development (R&D) methodology with the ADDIE development model comprising five stages: Analysis, Design, Development, Implementation, and Evaluation. Module validation involved experts in content, media, and language. The trial was conducted with 23 students of class XI-2. Two validators were assigned for each area. Results showed that the module achieved an overall validity score of 84.29%, categorized as valid. Its practicality reached 89.75%, categorized as practical. Student learning effectiveness reached 47%, showing the module is effective in improving learning outcomes. Therefore, the module is deemed feasible, engaging, and beneficial for enhancing student achievement.